2011
DOI: 10.4236/jsemat.2011.11002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Coolant in Machinability of Titanium Alloy (Ti-6Al-4V)

Abstract: Application of titanium alloy has increased many fields since the past 50 years. The major drawback encountered during machining was difficult to cut and the formation of BUE (Built up Edge). This paper presents the tool wear study of TTI 15 ceramic insert (80% Aluminum oxide and 20 % Titanium carbide) on machining Ti-6Al-4V at moderate speed with and without the application of water soluble servo cut S coolant. Titanium alloy is highly refractory metal and machining titanium is challenging to the manufacturer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Consequently, this improves surface finish of workpiece and the tool life. Namb and Paulo [62] investigated machinability of Ti-6Al-4V at varied cutting speed of 45, 90, 135 m/min, depth of cut of 0.5 and 0.75 mm and feed rate of 0.1,0.2 and 0.3 mm/ rev. They found that tool life increased by 30% in comparison with dry machining when cutting fluid containing 75% water was applied.…”
Section: Lubricationmentioning
confidence: 99%
“…Consequently, this improves surface finish of workpiece and the tool life. Namb and Paulo [62] investigated machinability of Ti-6Al-4V at varied cutting speed of 45, 90, 135 m/min, depth of cut of 0.5 and 0.75 mm and feed rate of 0.1,0.2 and 0.3 mm/ rev. They found that tool life increased by 30% in comparison with dry machining when cutting fluid containing 75% water was applied.…”
Section: Lubricationmentioning
confidence: 99%
“…An alternative to machining without a cutting fluid is flood cooling. Compared with dry machining, it has been found to significantly improve surface quality, reduce total blade wear by 30%, minimize diffusive and adhesive wear, and substantially reduce the adhesion of chips to the blade's face, increasing productivity [3,4]. Even better results are achieved when the cutting fluid is fed under pressure.…”
Section: Introductionmentioning
confidence: 99%
“…The use of inserts further increased machinability of the titanium alloy. The influence of coolant on machining Ti-6Al-4V has also been investigated [12]. Findings showed an improved Ra value of 1.3µm with coolant as against 1.4µm without coolant.…”
Section: Introductionmentioning
confidence: 99%